Love in the Holy Qur'an - Ghazi bin Muhammad (Lahore Ilqa Publication, 2022)
Summary:"Examining at least one verse from every chapter of the Qur'an, and citing more than one-fifth of the entire text, this study analyzes what the Islamic holy book has to say about love. More than simply exploring the well-trodden subjects of love of God and love of neighbor, however, this book discusses familial love, friendship, the stages of falling in love, sexual love, extramarital love, beauty, taste, and many more. This work is essential reading not only for Muslims and scholars of Islam and Qur'an, but anyone interested in the secrets and mysteries of love."
Include Bibliography and Index
Keywords: Islam and Quran